Latest seasonal trend of aerosol, particulate matter and ozone in Delhi - CHAKRABARTY , D. K.; PESHIN, S. K. (MAUSAM, 2016)
In this work, latest seasonal variation of aerosol, particulate matter and ozone in Delhi has been studied. Observations show that during winter, concentration of surface O3 is low and that of PM2.5 and PM10 is high. Aerosol size and aerosol content increases during winter. Decrease in surface ozone is explainable by gas phase and heterogeneous chemistry. An interesting feature is, along with surface ozone, total ozone also shows a low value during winter. This is a characteristic of ozone in Indo-Gangetic plain. Indo-Gangetic plain is covered by mild to heavy fog during most of the days in winter. It is possible that increase in size and content of aerosol and PM particles coupled with low temperature, low solar flux and high humidity is the cause of fog formation during winter in Indo-Gangetic plain.